Effect of crosswinds on aerodynamic characteristics around a generic train model - Ishak, I. A.; Mat Ali, Mohamed Sukri; Mohd Yakub, Mohamad Fitri; Shaikh Salim, Sheikh Ahmad Zaki (Taylor & Francis Group, 2019)
In this article, simulations of crosswinds over a rectangular prism with two types of train nose shapes (i.e. blunt and ellipse) that are running on flat ground case are discussed. The incident flow angle is varied from 0° to 90°. The flow around the train is solved using the incompressible form of the unsteady Reynolds Navier-Stokes (URANS) equations combined with the Shear-Stress-Transport k ω turbulence model. The Reynolds number used, based on the height of the train is 3.7 × 105 . Two distinctive flow regimes appear which represent a slender body behaviour at a smaller range of incident flow angles (below 45°) and bluff body behaviour at a much higher range of incident flow angles (above 45°). The safety guidelines for train’s operation suggested that both the train’s nose geometry and the wind speed condition are the two major factors that limit the maximum allowable speed for a particular train to be travelling.